Work Placement Supervisor Support and Students' Proactive Career Behaviors: The Moderating Role of Proactivity. (February 2023) - Okolie, Ugochukwu Chinonso; Mlanga, Sunday; Nwosu, Hyginus E.; Mezieobi, Kelechi; Okorie, Cornelius Ofobuisi; Abonyi, Sunday O.
Drawing upon social cognitive career theory model of career self-management, we examined the relationship between work placement supervisor support (WPSS) and students' proactive career behaviors (PCB), mediating role of work placement learning self-efficacy and the moderating effect of proactivity in the indirect relationships. Data were collected from 275 university undergraduate students undertaking placement learning in 129 firms. The regression analysis revealed that WPSS associated positively with all the constructs of PCB namely: career planning, proactive skills development, career consultation, and career network building, as well as work placement learning self-efficacy. Also, work placement learning self-efficacy mediated the relationship between WPSS and the constructs of PCB except career consultation. Proactivity moderated the relationship between work placement learning self-efficacy and career planning and career network building, and the indirect effects of WPSS on career planning and career network building via work placement learning self-efficacy were significant at low, average, and high levels.